Rangkap Jabatan Menteri dalam Konteks Kepentingan Negara Berdasarkan Asas – Asas Umum Pemerintahan yang Baik Perspektif Siyasah Tanfidziyah - Amin Rahmad Panjaitan; Irwansyah Irwansyah (UNES Law Review, 2023)
Rangkap jabatan" is a term in Indonesian that refers to an individual holding multiple positions in different companies or institutions. In Indonesia, the issue of ministers holding multiple positions has become controversial. The purpose is to understand the laws and general principles of good governance that apply. The author uses a normative juridical research method to analyze every writing, rule, and its application. Based on Article 23 of Law Number 39 of 2008, it is stated that ministers are prohibited from holding multiple positions as other officials in accordance with laws and regulations, commissioners or directors of state-owned or private companies, and leaders of organizations funded by the State Revenue and Expenditure Budget/Regional Revenue and Expenditure Budget. Meanwhile, in Article 10 of Law Number 30 of 2014, it is stated that officials in carrying out their duties must be based on the principles of Good Governance and must not be contradictory. In Indonesia, there are several ministers who hold positions as chairman of political parties and other large organizations at the same time. This is certainly contrary to the applicable rules. It is concluded that the practice of ministers holding multiple positions in Indonesia as chairman of political parties and leaders of other large organizations is contrary to the explanation of Article 23 of Law Number 39 of 2008 and Article 10 of Law Number 30 of 2014. Based on the perspective of siyasah tandfiziyyah, holding multiple positions by ministers in Indonesia is not in accordance with one of the principles used in the Islamic governance system.